Brazil : Interest Rates and Intermediation Spreads - World Bank (Washington, DC, 2015)
This study sheds light on the analytical and policy issues regarding the high intermediation spread in Brazil, focusing on its determinants, the reasons for its persistence, and its impact on the real economy, especially on access to finance for Brazilian firms. The key contention of the analysis is that high intermediation spreads are a symptom of underlying problems; as such, spreads constitute a window that, when open appropriately and under the right analytical light, can unveil deeper issues concerning the Brazilian financial system, its functioning, and its linkages to economic performance. The study's major contribution is to investigate the level of intermediation spreads in Brazil from macro, micro, and international perspectives. In particular, the international perspective compares the Brazilian financial system with industrialized countries and Latin American peers to provide a background for the analysis, and highlight the areas where Brazil appears to be special.